Cerebral aspergillosis in the era of new antifungals: The CEREALS national cohort study Nationwide CEREbral Aspergillosis Lesional study (CEREALS). Issue 2 (February 2022) - Serris, A.; Benzakoun, J.; Danion, F.; Porcher, R.; Sonneville, R.; Wolff, M.; Kremer, S.; Letscher-Bru, V; Fekkar, A; Hekimian, G.; Pourcher, V.; Bougnoux, M-E.; et al.
Highlights: Characteristics of cerebral aspergillosis vary according to the presumed route of Aspergillus dissemination to the brain. Galactommanan antigen is positive in the sera in 61% of the patients and in the CSF in 69%. CSF analysis is often informative and should be formed systematically if possible. Cerebral ischemic events are reported in 2/3 of patients with cerebral aspergillosis with contiguous extension. Cerebral aspergillosis mortality remains high (45% at W6 and 63% at M12). Summary: Background: Cerebral aspergillosis (CA) is a life-threatening disease for which diagnosis and management remain challenging. Detailed analyses from large cohorts are lacking. Methods: We included 119 cases of proven ( n = 54) or probable ( n = 65) CA diagnosed between 2006 and 2018 at 20 French hospitals. Data were collected at baseline and during follow-up. Cerebral imaging was reviewed centrally by two neuroradiologists. Results: The most frequent underlying conditions were hematological malignancy (40%) and solid organ transplantation (29%). Galactomannan was detected in the serum of 64% of patients. In 75% of cases, at least one of galactomannan, Aspergillus PCR, and β-d -glucan was positive in the cerebrospinal fluid. Six-week mortality was 45%. Two distinct patterns of disease were identified according to presumed route of dissemination. Presumed haematogenous dissemination ( n = 88) was associated with a higher frequency of impaired consciousness (64%), shorter time to diagnosis, the presence of multiple abscesses (70%), microangiopathy (52%), detection of serum galactomannan (69%) and Aspergillus PCR (68%), and higher six-week mortality (54%). By contrast, contiguous dissemination from the paranasal sinuses ( n = 31) was associated with a higher frequency of cranial nerve palsy (65%), evidence of meningitis on cerebral imaging (83%), macrovascular lesions (61%), delayed diagnosis, and lower six-week mortality (30%). In multivariate analysis and in a risk prediction model, haematogenous dissemination, hematological malignancy and the detection of serum galactomannan were associated with higher six-week mortality. Conclusion: Distinguishing between hematogenous and contiguous dissemination patterns appears to be critical in the workup for CA, as they are associated with significant differences in clinical presentation and outcome. Graphical abstract: Summary of clinical, mycological and radiological major characteristics of CA Image, graphical abstract .